(untitled) (Journal of Enam Medical College, 2016)
Background: Dysfunctional uterine bleeding (DUB) is irregular uterine bleeding that occurs in the absence of recognizable pelvic pathology, general medical disease, or pregnancy. It reflects a disruption in the normal cyclic pattern of ovulatory hormonal stimulation to the endometrial lining. About 12% of women with improperly managed anovulatory bleeding eventually may develop endometrial cancer but determinants behind the disease are largely unknown. Objective: The present study aimed to find out the determinants of dysfunctional uterine bleeding. Materials and Methods: In this cross-sectional study 50 patients of dysfunctional uterine bleeding (DUB) were recruited from different tertiary hospitals in Dhaka city. Clinical parameters have been recorded using a predesigned questionnaire and analyzed using SPSS for Windows version 16.0 and Microsoft Office Excel. Results: In the studied patients, about 38% were suffering from type 2 diabetes mellitus, 12% from obesity and 18% from hypertension. Almost all the patients (96%) were suffering from anemia. Histological findings have shown that endometrium of 63% patients were in proliferative phase, about 16% were in secretory phase and 11% patients were with cystic hyperplasia. Ultrasonographic results have shown that about 72% of the patients had bulky uterus. Ninety two percent patients carried more than two pregnancies, and 40% patients carried >5 pregnancies. Conclusion: Bulky uterus and multiple pregnancies may be associated with dysfunctional uterine bleeding in Bangladeshi women. J Enam Med Col 2016; 6(1): 23-27